Glucose-sensitive hypothalamic nuclei traced through functional magnetic resonance imaging - Manuel, Jorge; Halbe, Eva; Ewald, Ann Charlotte; Hoff, Alex; Jordan, Jens; Tank, Jens; Heusser, Karsten; Gerlach, Darius A. (Frontiers in Neuroscience, 2023)
Hypothalamic glucose-sensitive neural circuits, which regulate energy metabolism and can contribute to diseases such as obesity and type 2 diabetes, have been difficult to study in humans. We developed an approach to assess hypothalamic functional connectivity changes during glucose loading using functional magnetic resonance imaging (fMRI). To do so, we conducted oral glucose tolerance tests while acquiring functional images before, and 10 and 45 minutes after glucose ingestion in a healthy male and cross-sectionally in 20 healthy participants on two different diets. At group level, 39 fMRI sessions were not sufficient to detect glucose-mediated connectivity changes. However, ten repeated sessions in a single subject revealed significant intrinsic functional connectivity increases 45 minutes after glucose intake in the arcuate, paraventricular, and dorsomedial nuclei, as well as in the posterior hypothalamic area, median eminence, and mamillary bodies. Our methodology allowed to outline glucose-sensitive hypothalamic pathways in a single human being and holds promise in delineating individual pathophysiology mechanisms in patients with dysglycemia.